Commentaires sur le Dhammapada - Mother, 1878-1973 (Sri Aurobindo Ashram, 1974)
Comprises talks on the Buddhist canonical work Dhammapada, delivered by The Mother to the inmates of Sri Aurobindo Ashram, 1957-1959.